2015
DOI: 10.1038/modpathol.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the class 1 histone deacetylases HDAC8 and 3 are associated with improved survival of patients with metastatic melanoma

Abstract: Prior studies have shown that combinations of histone deacetylase (HDAC) and BRAF inhibitors (BRAFi) have synergistic effects on BRAFi-resistant melanoma through enhanced apoptosis and inhibition of the cAMPdependent drug resistance pathway. However, little is known about the expression of various HDACs and their associations with BRAF/NRAS mutation status, clinicopathologic characteristics, and patient outcome. The present study extensively profiled HDAC class 1 and their targets/regulators utilizing immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Similarly, the analysis of publicly available databases including the Cancer Genome Atlas and the Cancer Cell encyclopedia did not identify any significant relationship between HDAC8 and CD274 mRNA expression. Although HDAC8 is frequently upregulated and the increase is associated with BRAF or NRAS mutation status in melanoma (Wilmott et al, 2015), PD-L1 is subject to regulation by a wide variety of mechanisms (Chen et al, 2016;Kataoka et al, 2016;Pardoll, 2012;Ribas, 2015). It is therefore not surprising that although HDAC8 is involved in regulation of PD-L1 expression, there is no linear relationship between HDAC8 and PD-L1 expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the analysis of publicly available databases including the Cancer Genome Atlas and the Cancer Cell encyclopedia did not identify any significant relationship between HDAC8 and CD274 mRNA expression. Although HDAC8 is frequently upregulated and the increase is associated with BRAF or NRAS mutation status in melanoma (Wilmott et al, 2015), PD-L1 is subject to regulation by a wide variety of mechanisms (Chen et al, 2016;Kataoka et al, 2016;Pardoll, 2012;Ribas, 2015). It is therefore not surprising that although HDAC8 is involved in regulation of PD-L1 expression, there is no linear relationship between HDAC8 and PD-L1 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that exposure to HDAC8 inhibitors may exacerbate immunosuppression in tumor-bearing hosts. Interestingly, high expression of HDAC8 is associated with improved survival of patients with metastatic melanoma (Wilmott et al, 2015). Whether this is related to suppression of PD-L1 thus permitting attack of melanoma cells by T cells remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that HDAC8 could serve as the prognostic biomarker, promote tumorigenesis and progress in multiple tumors. For example, Wilmott et al (36) found that HDAC8 may be a prognostic biomarker in melanoma, and also provide important data regarding the regulation of HDACs in melanoma and a rational basis for targeting them therapeutically; Wu et al (22) reported that HDAC8 was overexpressed in HCC and HDAC8 knockdown could suppress tumor growth and enhance apoptosis in HCC via elevating the expression of p53 and acetylation of p53 at Lys382, indicating that HDAC8 might serve as a potential therapeutic target in HCC (37); Oehme et al (16) found that the knockdown of HDAC8 resulted in the inhibition of proliferation, reduced clonogenic growth, cell cycle arrest and differentiation in cultured neuro blastoma cells; Balasubramanian et al (38) reported that HDAC8-selective inhibitors had a unique mechanism of action involving PLCγ1 activation and calcium-induced apoptosis, and could offer benefits including a greater therapeutic index for treating T-cell malignancies. In the present study, we also found that depletion of HDAC8 using small interference RNA promoted apoptosis and cell cycle arrest in gastric cancer cells, moreover, forced expression of HDAC8 inhibited cell apoptosis and promoted cell proliferation, which suggested that HDAC8 may be a potential therapeutic target of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about HDAC expression in melanoma. HDAC8 expression is associated with improved survival in melanoma, but HDAC1 and HDAC8 also correlate with increase phosphorylated p65—a subunit of the NF-κB complex, which is associated with resistance to MAPK inhibitors [ 36 , 37 ].…”
Section: Epigenetic Changes—a Brief Overviewmentioning
confidence: 99%